A double network hydrogel based on pre-embedded inorganic micro-nanoparticles and its preparation method and application

By pre-embedding inorganic micro-nanoparticles in the hydrogel and triggering Ca2+ ion cross-linking to form a dual network structure, the problem of insufficient mechanical strength and conductivity of traditional hydrogels is solved, and water with high mechanical properties and conductivity is achieved Gel, suitable for a variety of application areas.

CN115819800BActive Publication Date: 2024-12-27SHANDONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211520183.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2024-12-27
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

The low mechanical strength and insufficient conductivity of conventional hydrogels limit their applications in flexible sensor materials, especially in high sensitivity sensing requirements.

Method used

Using the preparation method of dual network hydrogel with pre-embedded inorganic micro-nanoparticles, calcium carbonate particles are added to sodium alginate/polyacrylamide hydrogel and Ca2+ ion crosslinking is triggered in acidic solution to form uniform crosslinking. dual network structure.

Benefits of technology

Hydrogels with high mechanical properties and conductive properties have excellent tensile strength, tensile properties, fracture toughness and strain sensitivity, and are suitable for wearable devices, motion detection and medical diagnosis and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115819800B_ABST
    Figure CN115819800B_ABST
Patent Text Reader

Abstract

The present invention discloses a double network hydrogel based on pre-embedded inorganic micro-nano particles and its preparation method and application, belonging to the technical field of polymer hydrogel. The preparation method of the present invention comprises mixing inorganic micro-nano particles in polymer and monomer solution, initiating polymerization and cross-linking of hydrogel monomers, obtaining a single network hydrogel embedding inorganic micro-nano particles, triggering the dissolution of inorganic micro-nano particles and releasing metal ions, thereby cross-linking the polymer to obtain a uniformly cross-linked double network hydrogel. The obtained double network hydrogel has excellent mechanical properties, high strain sensitivity, good durability, can be used as a strain sensor to monitor human body movement, and has a fast response speed. In addition, it can be used as a sensor to monitor pain signals caused by cascade reactions at the wound surface of diabetic rat models in situ.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer hydrogels, and in particular relates to a double network hydrogel based on pre-embedded inorganic micro-nano particles, and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Hydrogel is a unique soft material with a three-dimensional network structure that can absorb and retain a large amount of aqueous solution. Due to its excellent biocompatibility and size-adjustable porous structure, hydrogel has broad application prospects in the fields of tissue engineering, adhesives, actuators, and sensors. However, due to the uneven structure of the gel network or the lack of an effective energy dissipation mechanism, traditional hydrogels have low mechanical strength and limited functions, which seriously restricts their application in many fields. In order to broaden the application of hydrogels, people are committed to developing new hydrogels with high mechanical strength.

[0004] Chinese patent CN109503757A discloses a novel double network hydrogel, which uses sodium alginate and monovalent cations to construct a sodium alginate supramolecular hydrogen bond reversible network, and then composites with a polyacrylamide cross-linked network to achieve the enhancement of the hydrogel. However, the double network hydrogel mainly relies on monovalent cations to induce sodium alginate to form a supramolecular fiber network to enhance the mechanical strength of the hydrogel. Its mechanical properties need to be improved, and its conductivity cannot meet the application requirements of high-sensitivity sensing. Therefore, how to prepare a hydrogel with excellent mechanical properties and conductive properties as a flexible sensor material has become a technical problem that needs to be solved at present. Summary of the invention

[0005] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide a double-network hydrogel based on pre-embedded inorganic micro-nanoparticles and a preparation method and application thereof. The present invention provides a simple and controllable strategy for designing and manufacturing double-network hydrogels with high mechanical properties, and has broad application prospects in the fields of wearable devices, motion detection, and medical diagnosis.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] On the one hand, a method for preparing a double network hydrogel based on pre-embedded inorganic micro-nanoparticles comprises the following steps:

[0008] Add hydrogel monomer B and inorganic micro-nanoparticles to the hydrogel monomer A solution, stir evenly, then add a crosslinker, an initiator and a catalyst, heat and polymerize to initiate the crosslinking of the hydrogel monomer B, and obtain a single-network hydrogel encapsulating inorganic micro-nanoparticles. Immerse it in an acidic solution to trigger the dissolution of the inorganic micro-nanoparticles to initiate the crosslinking of the hydrogel monomer A, and obtain a uniformly crosslinked double-network hydrogel.

[0009] On the other hand, the above-mentioned preparation method of double network hydrogel based on pre-embedded inorganic micro-nanoparticles obtains a uniformly cross-linked double network hydrogel.

[0010] The double network hydrogel prepared by the present invention has high strain sensitivity, a wide strain detection range, good stability, and a fast response speed. Therefore, in the third aspect, the double network hydrogel is used in a flexible sensor.

[0011] The beneficial effects of the present invention are:

[0012] (1) The preparation method of the present invention is simple and easy to implement. The present invention pre-embeds CaCO3 particles in a sodium alginate / polyacrylamide (SA / PAM) hydrogel, and then triggers CaCO3 in an acidic solution. 2+ The release of Ca 2+ Ionic crosslinking with carboxyl groups is performed to obtain a double network hydrogel with uniform crosslinking and excellent mechanical properties. The present invention provides a simple, controllable and universal method for preparing a double network hydrogel with uniform crosslinking and high mechanical properties.

[0013] (2) The double network hydrogel obtained by the preparation method of the present invention has excellent tensile strength (0.85 MPa), stretchability (1850%) and fracture toughness (6.4 MJ / m -3 );

[0014] (3) The double network hydrogel obtained by the preparation method of the present invention has a strain sensitivity of up to 8.9, a wide strain detection range (0.03-1800%), and good durability (can be cycled 500 times at 50% strain). It can be used as a strain sensor to monitor the movement of humans and mice, and has a fast response speed (0.02s). In addition, the pain signal caused by the cascade reaction at the wound surface of the diabetic rat model can also be monitored in situ. The present invention provides a simple and controllable strategy for the engineering design of stretchable and tough double network hydrogels, and has broad application prospects in the fields of wearable devices, motion detection, and medical diagnosis. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0016] Figure 1 is Ca in Example 1 of the present invention 2+ Schematic diagram of the preparation of / SA / PAM double network hydrogel;

[0017] Figure 2 The CaCO3 / SA / PAM hydrogel and Ca in Example 1 of the present invention 2+ / SA / PAM double network hydrogel SEM image;

[0018] Figure 3 is Ca in Example 1 of the present invention 2+ Image of element distribution in / SA / PAM double network hydrogel;

[0019] Figure 4 is Ca in Example 1 of the present invention 2+ Macroscopic photos of mechanical properties of / SA / PAM double network hydrogels;

[0020] Figure 5 is the CaCO3 concentration of the present invention. 2+ / SA / PAM double network hydrogel tensile mechanical properties curve;

[0021] Figure 6 is the CaCO3 concentration of the present invention. 2+ / SA / PAM dual network hydrogel fracture toughness diagram;

[0022] Figure 7 The tensile mechanical property curves of the SA / PAM hydrogels with different hydrochloric acid immersion times of the present invention;

[0023] Figure 8 The fracture toughness diagram of the SA / PAM double network hydrogel with different hydrochloric acid immersion time of the present invention;

[0024] Fig. 9 is Ca in Example 1 of the present invention 2+ / SA / PAM double network hydrogel relative resistance change curve with tensile strain;

[0025] Fig.10 is Ca in Example 1 of the present invention 2+ / SA / PAM dual network hydrogel is used as a strain sensor to monitor the curve of human motion changes;

[0026] Fig.11 is Ca in Example 1 of the present invention 2+ Response time of / SA / PAM dual network hydrogel as strain sensor;

[0027] Fig.12 is Ca in Example 1 of the present invention 2+ / SA / PAM double network hydrogel was used as a strain sensor to monitor the movement curve of mice;

[0028] Fig.13 is Ca in Example 1 of the present invention 2+ / SA / PAM dual network hydrogel as strain sensor combined with MS / GOx@TA / Fe 2+ Schematic diagram of NPs in situ monitoring of pain signals caused by cascade reactions;

[0029] Fig.14 is Ca in Example 1 of the present invention 2+ / SA / PAM dual network hydrogel as strain sensor combined with MS / GOx@TA / Fe 2+ NPs in situ monitor the real-time resistance changes of pain signals caused by cascade reactions. DETAILED DESCRIPTION

[0030] In view of the current lack of methods for preparing hydrogels with both excellent mechanical properties and conductive properties, the present invention proposes a double-network hydrogel based on pre-embedded inorganic micro-nanoparticles and a preparation method and application thereof.

[0031] A typical embodiment of the present invention provides a method for preparing a double network hydrogel based on pre-embedded inorganic micro-nanoparticles, comprising the following steps:

[0032] Add hydrogel monomer B and inorganic micro-nanoparticles to the hydrogel monomer A solution, stir evenly, then add a crosslinker, an initiator and a catalyst, heat and polymerize to initiate the crosslinking of the hydrogel monomer B, and obtain a single-network hydrogel encapsulating inorganic micro-nanoparticles. Immerse it in an acidic solution to trigger the dissolution of the inorganic micro-nanoparticles to initiate the crosslinking of the hydrogel monomer A, and obtain a uniformly crosslinked double-network hydrogel.

[0033] In some examples of this embodiment, the hydrogel monomer A is selected from one or more of sodium alginate, chitosan, carboxymethyl chitosan, hyaluronic acid and / or chondroitin sulfate, preferably sodium alginate.

[0034] In some examples of this embodiment, the concentration of the hydrogel monomer A solution is 0.1-40 mg / mL, and more preferably 5-20 mg / mL.

[0035] In some examples of this embodiment, the inorganic micro-nanoparticles are selected from one or more of calcium carbonate, barium carbonate, zinc carbonate, barium hydroxide, magnesium hydroxide, zinc hydroxide, calcium sulfite, barium sulfite, zinc sulfite, calcium silicate, barium silicate, magnesium silicate, zinc silicate, calcium phosphate, barium phosphate, magnesium phosphate, zinc phosphate, calcium oxalate, barium oxalate, zinc oxalate, barium chromate, aluminum hydroxide, iron hydroxide, iron sulfide, aluminum sulfite, aluminum silicate, iron silicate, aluminum phosphate, iron phosphate, aluminum oxalate, and / or iron oxalate, preferably calcium carbonate.

[0036] The concentration of the inorganic micro-nano particles in the hydrogel monomer A is 1-20 mg / mL, and more preferably 1-5 mg / mL.

[0037] In some examples of this embodiment, the hydrogel monomer B is selected from one or more of acrylamide, N,N-diethylacrylamide, N-isopropylacrylamide, N-isobutylacrylamide and / or N-tert-butylacrylamide, preferably acrylamide.

[0038] In some examples of this embodiment, the concentration of the hydrogel monomer B in the hydrogel monomer A solution is 100-800 mg / mL, and more preferably 240-480 mg / mL.

[0039] In some examples of this embodiment, the cross-linking agent is selected from one or more of N,N'-methylenebisacrylamide, N,N'-bis(acryloyl)cystamine, N,N'-diallyltartaric acid diamide, divinylbenzene, polyethylene glycol diacrylate and / or polyethylene glycol dimethacrylate, preferably N,N'-methylenebisacrylamide.

[0040] In some examples of this embodiment, the initiator is one or more of ammonium persulfate, potassium persulfate, sodium persulfate, benzoyl peroxide and / or azobisisobutylamidine hydrochloride, preferably ammonium persulfate.

[0041] In some examples of this embodiment, the catalyst is one or more of N,N,N',N'-tetramethylethylenediamine, sodium sulfite, sodium bisulfite and / or sodium thiosulfate, preferably N,N,N',N'-tetramethylethylenediamine.

[0042] In some examples of this embodiment, the mass ratio of the cross-linking agent to the hydrogel monomer B is 0.0001-0.0015:1, and more preferably 0.0003-0.0012:1.

[0043] In some examples of this embodiment, the mass ratio of the initiator to the hydrogel monomer B is 0.0005-0.003:1, and more preferably 0.001:1.

[0044] In some examples of this embodiment, the mass ratio of the catalyst to the hydrogel monomer B is 0.001-0.004:1, and more preferably 0.0025:1.

[0045] In some examples of this embodiment, the stirring time is 0.5-4h, preferably 2h.

[0046] In some examples of this embodiment, the cross-linking agent, initiator and catalyst are added and then stirred for 5-30 minutes, more preferably 10 minutes.

[0047] In some examples of this embodiment, the heating polymerization reaction conditions are: reaction at 40-60°C for 0.5-6h, and more preferably, reaction at 50°C for 3h.

[0048] In some examples of this embodiment, the acidic solution is selected from one or more of hydrochloric acid, acetic acid, sulfuric acid, phosphoric acid and / or nitric acid, preferably hydrochloric acid.

[0049] The acid solution has a concentration of pH=1-3, and more preferably pH=2.

[0050] In some examples of this embodiment, the soaking time is 1-10 hours, and more preferably 1-6 hours.

[0051] Another typical embodiment of the present invention provides a uniformly cross-linked double network hydrogel obtained by the above-mentioned preparation method of the double network hydrogel pre-embedded with inorganic micro-nanoparticles.

[0052] A third typical embodiment of the present invention provides application of the double network hydrogel in a flexible sensor.

[0053] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0054] Example 1

[0055] A method for preparing a double network hydrogel based on pre-embedded inorganic micro-nano particles comprises the following steps:

[0056] (1) Accurately weigh 1 g of sodium alginate and dissolve it in 50 mL of ultrapure water. Stir it at 25 °C for 4 h, and then continue stirring in a 50 °C water bath for 0.5 h to obtain a dissolved sodium alginate solution.

[0057] (2) Add 16 g acrylamide and 0.15 g calcium carbonate particles to the above-dissolved sodium alginate solution, stir for 2 h, then add 0.0096 g N,N'-methylenebisacrylamide, 0.016 g ammonium persulfate, and 0.04 g N,N,N',N'-tetramethylethylenediamine, stir for 10 min, stir evenly, and finally pour the mixed solution into a mold and react at 50°C for 3 h to obtain sodium alginate / polyacrylamide (CaCO3 / SA / PAM) hydrogel encapsulating calcium carbonate particles.

[0058] (3) The CaCO3 / SA / PAM hydrogel was immersed in a hydrochloric acid solution (pH = 2) for 2 h to trigger the dissolution of calcium carbonate particles and obtain a sodium alginate / polyacrylamide (CaCO3 / SA / PAM) hydrogel uniformly cross-linked with calcium ions. 2+ / SA / PAM) double network hydrogel, see Figure 1 .

[0059] Example 2

[0060] A method for preparing a double network hydrogel based on pre-embedded inorganic micro-nano particles, which differs from Example 1 in that the mass of added calcium carbonate particles is changed from 0.15 g to 0.2 g.

[0061] Example 3

[0062] A method for preparing a double network hydrogel based on pre-embedded inorganic micro-nanoparticles, which is different from Example 1 in that the mass of sodium alginate is changed from 1 g to 0.5 g.

[0063] Example 4

[0064] A method for preparing a double network hydrogel based on pre-embedded inorganic micro-nano particles, which differs from Example 1 in that the mass of added acrylamide is changed from 16 g to 24 g.

[0065] Example 5

[0066] A method for preparing a double network hydrogel based on pre-embedded inorganic micro-nanoparticles, which differs from Example 1 in that the mass of added N,N'-methylenebisacrylamide is changed from 0.0096 g to 0.0144 g.

[0067] Example 6

[0068] A method for preparing a double network hydrogel based on pre-embedded inorganic micro-nanoparticles, which differs from Example 1 in that the time for immersing the CaCO3 / SA / PAM hydrogel in the hydrochloric acid solution is changed from 2 hours to 4 hours.

[0069] Example 7

[0070] A method for preparing a double network hydrogel based on pre-embedded inorganic micro-nano particles, which is different from Example 1 in that the inorganic micro-nano particles are aluminum hydroxide.

[0071] Comparative Example 1

[0072] In order to compare the effect of adding or not adding calcium carbonate particles on the mechanical properties of the hydrogel, a comparative example 1 was set. The difference between comparative example 1 and example 1 is that no calcium carbonate particles were added to obtain SA / PAM hydrogel.

[0073] Experimental Example 1: Hydrogel Performance Testing

[0074] (1) SEM test

[0075] The CaCO3 / SA / PAM hydrogel and Ca 2+ The morphology of the / SA / PAM double network hydrogel was characterized. Figure 2 It can be seen that CaCO3 / SA / PAM hydrogel is distributed with CaCO3 particles; when it is immersed in hydrochloric acid solution and subjected to acid stimulation, the CaCO3 particles dissolve into Ca 2+ , Ca 2+ The carboxyl groups on SA were cross-linked to form a denser fiber network. SEM mapping confirmed that Ca 2+ Uniform distribution in the hydrogel ( Figure 3 These results suggest that by triggering Ca from pre-embedded CaCO3 microparticles 2+ release, and uniformly cross-linked Ca 2+ / SA / PAM double network hydrogel.

[0076] (2) Mechanical properties test

[0077] First, the Ca obtained in Example 1 2+ The mechanical properties of the Ca / SA / PAM double network hydrogel were macroscopically characterized. 2 + The SA / PAM double network hydrogel can immediately recover its original shape after being squeezed, and can well withstand various deformations such as bending, knotting and stretching, with strong load-bearing capacity and excellent flexibility and elasticity. In addition, a hydrogel strip with a diameter of 5 mm can withstand a weight of 2 kg without any damage ( Figure 4 ). Then, the Ca2+ concentrations obtained were 2+ / SA / PAM double network hydrogel was quantitatively tested for tensile properties ( Figure 5 ) and fracture toughness test ( Figure 6 ). When the concentration of CaCO3 is 3 mg / mL, Ca 2+The tensile strength and tensile strain of the / SA / PAM double network hydrogel reached the maximum, which were 0.85MPa and 1850%, respectively. At this time, the fracture toughness of the hydrogel could reach 6.4MJ / m 3 ( Figure 6 ). The tensile strength and toughness of the SA / PAM hydrogels in Comparative Example 1 with different hydrochloric acid immersion times decreased from 0.27 to 0.15 MPa and from 1.78 to 0.58 MJ / m 3 ( Figure 7 , 8 ). This may be caused by the lack of ionic cross-linked network, thus the hydrogel swells under long-term incubation in HCl solution.

[0078] (3) Strain sensitivity experiment of hydrogel

[0079] The Ca obtained in Example 1 was further studied by measuring the change in relative resistance (ΔR / R0) under different tensile strains. 2+ Sensitivity of / SA / PAM double network hydrogels to tensile deformation ( Fig. 9 ). The GF represents the sensitivity of the hydrogel and is calculated from the relative resistance change-strain curve. The curve can be roughly divided into three linear regions, with GF values ​​of 2.1 (0-200%), 5.5 (200%-800%) and 8.9 (800%-1800%), which are better than most reported ion-conducting hydrogels.

[0080] (4) Ca 2+ / SA / PAM dual network hydrogel strain sensor for human motion monitoring

[0081] In order to study the potential application as a wearable strain sensor, the Ca obtained in Example 1 2+ / SA / PAM dual network hydrogel strips are installed in different parts of the human body to monitor human activities ( Fig.10 ).

[0082] Ca 2+ The relative resistance of the / SA / PAM dual network strain sensor increases as the finger gradually bends from the straight state to 120°, which is caused by the stretching of the hydrogel when the finger moves. In addition, when the finger returns to the straight state, the relative resistance change of the hydrogel also gradually recovers, indicating that this hydrogel has high sensitivity as a strain sensor. When it is tightly adhered to the knee, Ca 2+ The strain sensor of the / SA / PAM dual network hydrogel can feedback the movement of standing and sitting. Taking advantage of the excellent sensitivity of tensile strain, the hydrogel sensor is further used to distinguish the subtle movements of humans. For example, when the test subject makes an expression such as frowning, Ca 2+The strain sensor of the SA / PAM dual network hydrogel can also be accurately monitored. In addition, the strain sensor can quickly monitor and distinguish all these actions with a response time of about 0.02s ( Fig.11 ), it has broad application prospects in the fields of artificial intelligence, human motion monitoring, health management, etc. in real life.

[0083] (5) Ca 2+ / SA / PAM dual network hydrogel strain sensor for monitoring mouse movement

[0084] In addition to monitoring the physiological signals and movements of the human body, the Ca obtained in Example 1 2+ / SA / PAM dual network hydrogel sensor can also monitor the movement changes of mice in real time ( Fig.12 ). The regular and stable electrical signals outputted indicate that the mouse heartbeat is stable. When acupuncture is applied to the mouse leg, the resistance changes periodically as the leg trembles. It is worth noting that the highly sensitive Ca 2+ The SA / PAM dual-network hydrogel sensors have a strong ability to identify different degrees of stimulation. When different degrees of strong and weak stimulation are applied to the mouse tail, they can provide precise, reliable and quantitative electrical responses.

[0085] (6) Ca 2+ / SA / PAM dual network hydrogel strain sensor for in situ monitoring of cascade-induced pain

[0086] In order to further prove that the Ca 2+ / SA / PAM dual network hydrogel sensor with accurate monitoring capability, nanoparticles with cascade reaction (MS / GOx@TA / Fe 2+ NPs) were combined with hydrogels and used to detect pain signals caused by cascade reactions in diabetic wounds ( Fig.13 , 14 ). It is reported that reactive oxygen species have an effect on pain perception. In order to monitor pain signals, MS / GOx@TA / Fe 2+ NPs were used to treat the wound surface, inducing a cascade reaction in the wound area due to the presence of glucose, and then the hydrogel sensor was attached to the wound surface. 2+ When monitoring NPs, the resistance signal tends to be a straight line. 2+ / SA / PAM dual network hydrogel sensor with MS / GOx@TA / Fe 2+When NPs bind, changes in electrical signals can be observed. As the monitoring time increases, the resistance signal gradually becomes wider, which may be due to the increase in ·OH content, indicating that the degree of pain on the wound surface has increased. After about 20 minutes, the resistance signal becomes sharp again, which may be due to the reduction of ·OH, which relieves the pain. Therefore, Ca 2+ The monitoring performance of the / SA / PAM double network hydrogel for weak signals also demonstrates its ultrasensitive properties.

[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a double network hydrogel based on pre-embedded inorganic micro-nanoparticles, characterized in that: The steps include: Add hydrogel monomer B and inorganic micro-nano particles to a hydrogel monomer A solution, stir evenly, then add a crosslinking agent, an initiator and a catalyst, heat and polymerize to initiate crosslinking of hydrogel monomer B, and obtain a single-network hydrogel encapsulating inorganic micro-nano particles, which is then immersed in an acidic solution to trigger dissolution of inorganic micro-nano particles to initiate crosslinking of hydrogel monomer A, and obtain a uniformly crosslinked double-network hydrogel; The hydrogel monomer A is selected from one or more of sodium alginate, chitosan, carboxymethyl chitosan, hyaluronic acid and / or chondroitin sulfate; The hydrogel monomer B is selected from one or more of acrylamide, N,N-diethylacrylamide, N-isopropylacrylamide, N-isobutylacrylamide and / or N-tert-butylacrylamide.

2. The preparation method according to claim 1, characterized in that: The hydrogel monomer A is sodium alginate.

3. The preparation method according to claim 1, characterized in that: The concentration of the hydrogel monomer A solution is 0.1-40 mg / mL.

4. The preparation method according to claim 3, characterized in that: The concentration of the hydrogel monomer A solution is 5-20 mg / mL.

5. The preparation method according to claim 1, characterized in that: The inorganic micro-nanoparticles are selected from one or more of calcium carbonate, barium carbonate, zinc carbonate, barium hydroxide, magnesium hydroxide, zinc hydroxide, calcium sulfite, barium sulfite, zinc sulfite, calcium silicate, zinc silicate, calcium phosphate, barium phosphate, magnesium phosphate, zinc phosphate, calcium oxalate, barium oxalate, zinc oxalate, barium chromate, aluminum hydroxide, iron hydroxide, iron sulfide, aluminum sulfite, aluminum silicate, aluminum phosphate, iron phosphate and / or aluminum oxalate.

6. The preparation method according to claim 5, characterized in that: The inorganic micro-nano particles are calcium carbonate.

7. The preparation method according to claim 1, characterized in that: The concentration of the inorganic micro-nano particles in the hydrogel monomer A solution is 1-20 mg / mL.

8. The preparation method according to claim 7, characterized in that: The concentration of the inorganic micro-nanoparticles in the hydrogel monomer A solution is 1-5 mg / mL.

9. The preparation method according to claim 1, characterized in that: The hydrogel monomer B is acrylamide.

10. The preparation method according to claim 1, characterized in that: The concentration of the hydrogel monomer B in the hydrogel monomer A solution is 100-800 mg / mL.

11. The preparation method according to claim 10, characterized in that: The concentration of the hydrogel monomer B in the hydrogel monomer A solution is 240-480 mg / mL.

12. The preparation method according to claim 1, characterized in that: The crosslinking agent is selected from one or more of N,N'-methylenebisacrylamide, N,N'-bis(acryloyl)cystamine, N,N'-diallyltartaric acid diamide, divinylbenzene, polyethylene glycol diacrylate and / or polyethylene glycol dimethacrylate.

13. The preparation method according to claim 12, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide.

14. The preparation method according to claim 1, characterized in that: The initiator is one or more of ammonium persulfate, potassium persulfate, sodium persulfate, benzoyl peroxide and / or azobisisobutylamidine hydrochloride.

15. The preparation method according to claim 14, characterized in that: The initiator is ammonium persulfate.

16. The preparation method according to claim 1, characterized in that: The catalyst is one or more of N,N,N',N'-tetramethylethylenediamine, sodium sulfite, sodium bisulfite and / or sodium thiosulfate.

17. The preparation method according to claim 16, characterized in that: The catalyst is N,N,N',N'-tetramethylethylenediamine.

18. The preparation method according to claim 1, characterized in that: The mass ratio of the cross-linking agent to the hydrogel monomer B is 0.0001-0.0015:1; The mass ratio of the initiator to the hydrogel monomer B is 0.0005-0.003:1; The mass ratio of the catalyst to the hydrogel monomer B is 0.001-0.004:

1.

19. The preparation method according to claim 18, characterized in that: The mass ratio of the cross-linking agent to the hydrogel monomer B is 0.0003-0.0012:1; The mass ratio of the initiator to the hydrogel monomer B is 0.001:1; The mass ratio of the catalyst to the hydrogel monomer B is 0.0025:

1.

20. The preparation method according to claim 1, characterized in that: The stirring time is 0.5-4h; After adding the crosslinking agent, initiator and catalyst, stir for 5-30 minutes; The heating polymerization reaction conditions are: reaction at 40-60° C. for 0.5-6 hours.

21. The preparation method according to claim 20, characterized in that: The stirring time is 2h; After adding the crosslinking agent, initiator and catalyst, stir for 10 min; The heating polymerization reaction conditions are: reacting at 50° C. for 3 hours.

22. The preparation method according to claim 1, characterized in that: The acidic solution is selected from one or more of hydrochloric acid, acetic acid, sulfuric acid, phosphoric acid and / or nitric acid; The acid solution concentration is: pH = 1-3; The soaking time is 1-10 hours.

23. The preparation method according to claim 22, characterized in that: The acidic solution is hydrochloric acid; The acid solution concentration is: pH = 2; The soaking time is 1-6 hours.

24. A uniformly cross-linked double network hydrogel obtained by the preparation method of a double network hydrogel pre-embedded with inorganic micro-nanoparticles according to any one of claims 1 to 23.

25. Use of the double network hydrogel according to claim 24 in a flexible sensor.

Citation Information

Patent Citations

  • Preparation method of novel double-network hydrogel, and obtained double-network hydrogel and application thereof

    CN109503757A

  • Calcium alginate microcapsule, preparation method and application thereof

    CN102626399A

  • Preparation method of calcium alginate submicron gel particles

    CN107057085A